South East Europe Regular Economic Report, November 2011 - World Bank (World Bank, Washington, DC, 2017)
The recovery of global growth that started in 2010 began to weaken in 2011. During the first half the falloff was linked to the Tohoku nuclear disaster in Japan and high oil prices, but by the end of July, temporary effects from Tohoku were starting to fade and global industrial production was rising. However, since August the global economy has come under increasing stress from the sovereign debt problems in Europe, anemic growth in the US, and a slowdown in China and other main emerging markets. The latest leading indicators and forecasts point to a further slowdown in growth in Europe. Meanwhile, risks remain of a double-dip recession in the US and sharper slowdown in the large emerging economies. Near term developments depend critically on factors that are largely beyond the control of governments. As this is being written, leaders of the major European Union (EU) countries are still seeking to implement a set of credible policies to establish an orderly process for managing sovereign debt in Greece, to prevent risks from spreading to other economies in the euro zone, to recapitalize banks affected by likely sovereign debt write downs, and to establish a more unified and effective fiscal framework for euro zone (EZ) states. Uncertainty over their ability to successfully conclude this process, as well a series of ratings downgrades, stock market volatility and uncertainty over US deficit policies have shaken investor and business confidence and kept consumers wary. Most forecasters have already reduced their projections for global growth in the US and the EU by a percent or more.